Risk factors of radiotherapy‐induced cerebral microbleeds and serial analysis of their size compared with white matter changes: A 7T MRI study in 113 adult patients with brain tumors. Issue 3 (20th January 2019) - Morrison, Melanie A.; Hess, Christopher P.; Clarke, Jennifer L.; Butowski, Nicholas; Chang, Susan M.; Molinaro, Annette M.; Lupo, Janine M.
Abstract : Background: Although radiation therapy (RT) contributes to survival benefit in many brain tumor patients, it has also been associated with long‐term brain injury. Cerebral microbleeds (CMBs) represent an important manifestation of radiation‐related injury. Purpose: To characterize the change in size and number of CMBs over time and to evaluate their relationship to white matter structural integrity as measured using diffusion MRI indices. Study Type: Longitudinal, retrospective, human cohort. Population: In all, 113 brain tumor patients including patients treated with focal RT ( n = 91, 80.5%) and a subset of nonirradiated controls ( n = 22, 19.5%). Field Strength/Sequence: Single and multiecho susceptibility‐weighted imaging (SWI) and multiband, shell, and direction diffusion tensor imaging (DTI) at 7 T. Assessment: Patients were scanned either once or serially. CMBs were detected and quantified on SWI images using a semiautomated approach. Local and global fractional anisotropy (FA) were measured from DTI data for a subset of 35 patients. Statistical Tests: Potential risk factors for CMB development were determined by multivariate linear regression and using linear mixed‐effect models. Longitudinal FA was quantitatively and qualitatively evaluated for trends. Results: All patients scanned at 1 or more years post‐RT had CMBs. A history of multiple surgical resections was a risk factor for development of CMBs. The total number and volume of CMBs increased by 18% and 11% per year, respectively, although individual CMBs decreased in volume over time. Simultaneous to these microvascular changes, FA decreased by a median of 6.5% per year. While the majority of nonirradiated controls had no CMBs, four control patients presented with fewer than five CMBs. Data Conclusion: Identifying patients who are at the greatest risk for CMB development, with its likely associated long‐term cognitive impairment, is an important step towards developing and piloting preventative and/or rehabilitative measures for patients undergoing RT. Level of Evidence: 3 Technical Efficacy: Stage 4 J. Magn. Reson. Imaging 2019;50:868–877.